Localised Learning of Urban Planning & Policy in the Baltic Sea Region - Sutela Elina; Ruoppila Sampo; Rasinkangas Jarkko (Maklu, 2022)
The case study from the University of Turku is an initiative called “Localized learning of urban planning and policy in the Baltic Sea Region”. This initiative was a series of three courses, organised jointly by University of Turku (urban studies minor), Estonian University of Life Sciences (master’s programme of landscape architecture), and University of Latvia (master’s programme of spatial planning) together with Urban Riga (an urban activism NGO). Each university partner organised one “hands-on” multidisciplinary urban planning course in its home country, with students and teachers from each partner university participating each time. The courses took place in three consecutive years from 2016 to 2018.
The idea was to engage students to work with real-life urban planning questions in a locality and develop new ideas or approaches benefitting the local community and the municipality. Learning-wise, graduate students were to apply theoretical knowledge they already had into practice in co-operation with local stakeholders. Moreover, they were to gain experience in working in multi-disciplinary and international teams to address a relevant topic in which the municipality needed new ideas and approaches. The community helped to inform students about solutions that could work for them. The general conclusion is that the course in Turku was well organised, got excellent feedback, and was considered successful, beneficial, and rewarding for all participants (students, stakeholders, and teachers). While the student work was not put to use as it was, the ideas contributed to conceptualisation and clarification of the theme and hence helped in their part the City of Turku towards reaching the strategic goals in this complex long-term planning quest. The city officials reported that they are referring back to the course’s outcomes from time to time in various discussions. The results have become part of a broader process in which the final implementable ideas emerge, transform, and gradually consolidate. The course also became another success story for urbanism related collaboration between the city and universities, paving the way for future joint-initiatives in Engaged Learning.
Engaged Learning in Europe